Non-State Actors in Asymmetric Conflicts: What does It Mean and What Follows of It - L. V. Deriglazova (Международная аналитика, 2024)
The article examines the problem of the participation of non-state actors in armed conflicts in the post-war period. The study is based on the theory of asymmetric conflict, which offers hypotheses about the reasons for the paradoxical defeat of developed countries against relatively weak opponents, including non-state actors. The empirical basis of the study is armed conflict databases, which allow us to test sole observations and hypotheses about the characteristics of asymmetric armed conflicts. The study uses the databases of the Uppsala Conflict Data Program Project (Sweden) and the COSIMO Project (University of Heidelberg, Germany) as well as publications of the Stockholm International Peace Research Institute (SIPRI). The study shows that the phenomenon of asymmetric conflicts reflects several important patterns of armed conflicts in the post-war period: the predominance of intrastate over interstate conflicts; the internationalisation of armed conflicts through the involvement of other countries, international organisations or non-state actors; the direct or indirect involvement of great powers in such conflicts; and the majority of armed conflicts occurring in Asia, Africa and the Middle East. Post-war armed conflicts are often referred to as “proxy wars” because the direct participants in the conflict are supported by external actors –  states or non-state actors.  The issues in conflicts between states and non-state actors are often political in nature, and the fundamental distinction between domestic and foreign policy has been overcome. The post-war period shows a gradual change of attitude towards the participation of non-state actors in armed conflicts, which reflects the recognition of their legitimacy as participants in the conflict, the negotiation and conclusion of agreements on the cessation of hostilities. Non-state actors in armed conflicts are themselves legitimised as representing the interests of particular groups and the goals of their struggle. UN peacekeeping operations since the end of the Cold War confirm these changes. Research on the participation of non-state actors in armed conflict reveals a broadening of the agenda and methodology for the study of post-war armed conflict, reflecting significant changes in the practice of international relations. These changes concern who is recognised as a legitimate actor in international relations, what role non-state actors play in armed conflict, and how non-state actors are viewed by other actors in international relations – states, international governmental and non-governmental organisations.